Effects of tocotrienols on insulin secretion-associated genes expression of rat pancreatic islets in a dynamic culture - Chia, Ling Li; Jantan, Ibrahim; Chua, Kien Hui; Lam, Kok Wai; Rullah, Kamal; Mohd Aluwi, Mohd Fadhlizil Fasihi (Frontiers, 2016)
Tocotrienols (T3) are well-known for their antioxidant properties besides showing therapeutic potential in clinical complications such as hyperlipidemia induced by diabetes. The aim of this study was to determine the effects of δ-T3, γ-T3, and α-T3 on insulin secretion-associated genes expression of rat pancreatic islets in a dynamic culture. Pancreatic islets freshly isolated from male Wistar rats were treated with T3 for 1 h at 37°C in a microfluidic system with continuous operation. The cells were collected for total RNA extraction and reverse-transcribed, followed by measurement of insulin secretion-associated genes expression using quantitative real-time polymerase chain reaction. Molecular docking experiments were performed to gain insights on how the T3 bind to the receptors. Short-term exposure of δ- and γ-T3 to pancreatic β cells in a stimulant glucose condition (16.7 mM) significantly regulated preproinsulin mRNA levels and insulin gene transcription. In contrast, α-T3 possessed less ability in the activation of insulin synthesis level. Essentially, potassium chloride (KCl), a β cell membrane depolarising agent added into the treatment further enhanced the insulin production. δ- and γ-T3 revealed significantly higher quantitative expression in most of the insulin secretion-associated genes groups containing 16.7 mM glucose alone and 16.7 mM glucose with 30 mM KCl ranging from 600 to 1200 μM (p < 0.05). The findings suggest the potential of δ-T3 in regulating insulin synthesis and glucose-stimulated insulin secretion through triggering pathway especially in the presence of KCl.